Customized toric intraocular lens implantation in cornea plana. Issue 12 (December 2020) - Fogla, Rajesh; Indumathy, Thazethaeveetil R.
Abstract : Cataract surgery with customized IOL is a good option to improve visual acuity in eyes with cornea plana. Abstract : A 50-year-old woman with cornea plana had reduced visual acuity due to development of lenticular changes. Flat keratometry with high astigmatism, shallow anterior chamber depth, and short axial length made it challenging both for intraocular lens (IOL) power calculation and cataract surgery. Surgery was planned for the right eye because the left eye was densely amblyopic. IOL power required was beyond the commercially available lenses; hence, a customized toric IOL was obtained. Phacoemulsification was successfully performed along with in-the-bag implantation of the toric IOL, which resulted in improved visual acuity with satisfactory refractive outcome. Cataract surgery with a customized IOL improved visual acuity in an eye with cornea plana.